Early argatroban and antiplatelet combination therapy in acute non-lacunar single subcortical infarct associated with mild intracranial atherosclerosis - Peng-Fei Wang (BMC, 2021)
Abstract Background Patients with acute non-lacunar single subcortical infarct (SSI) associated with mild intracranial atherosclerosis (ICAS) have a relatively high incidence of early neurological deterioration (END), resulting in unfavorable functional outcomes. Whether the early administration of argatroban and aspirin or clopidogrel within 6–12 h after symptom onset is effective and safe in these patients is unknown. Methods A review of the stroke database of Weihai Municipal Hospital, Cheeloo College of Medicine, Shandong University and Qingdao Center Hospital, Qingdao University Medical College in China was undertaken from May 2017 to January 2020 to identify all patients with non-lacunar SSI caused by ICAS within 6–12 h of symptom onset based on MRI screening. Patients were divided into two groups, one comprising those who received argatroban and mono antiplatelet therapy with aspirin or clopidogrel on admission (argatroban group), and the other those who received dual antiplatelet therapy (DAPT) with aspirin and clopidogrel during hospitalization (DAPT group). The primary outcome was recovery by 90 days after stroke based on a modified Rankin scale (mRS) score (0 to 1). The secondary outcome was END incidence within 120 h of admission. Safety outcomes were intracranial hemorrhage (ICH) and major extracranial bleeding. The probability of clinical benefit (mRS score 0–1 at 90 days) was estimated using multivariable logistic regression analysis. Results A total of 304 acute non-lacunar SSI associated with mild ICAS patients were analyzed. At 90 days, 101 (74.2%) patients in the argatroban group and 80 (47.6%) in the DAPT group had an mRS score that improved from 0 to 1 (P < 0.001). The relative risk (95% credible interval) for an mRS score improving from 0 to 1 in the argatroban group was 1.50 (1.05–2.70). END occurred in 10 (7.3%) patients in the argatroban group compared with 37 (22.0%) in the DAPT group (P < 0.001). No patients experienced symptomatic hemorrhagic transformation. Conclusions Early combined administration of argatroban and an antiplatelet agent (aspirin or clopidogrel) may be beneficial for patients with non-lacunar SSI associated with mild ICAS identified by MRI screening and may attenuate progressive neurological deficits. Trial registration Our study is a retrospectively registered trial.